Respostas
respondido por:
1
a) x² - 6x + 5 = 0
a = 1; b = -6; c = 5
x = [- b ± √(b² - 4ac)] / 2a
x = [- (-6) ± √([-6]² - 4 . 1 . 5)] / 2 . 1
x = [6 ± √(36 - 20)] / 2
x = [6 ± √16] / 2
x = [6 ± 4] / 2
x' = [6 + 4] / 2 = 10 / 2 = 5
x'' = [6 - 4] / 2 = 2 / 2 = 1
S = {1, 5}
b) -x² + 6x - 5 = 0
x = [- b ± √(b² - 4ac)] / 2a
x = [- 6 ± √(6² - 4 . [-1] . [-5])] / 2 . (-1)
x = [- 6 ± √(36 - 20)] / -2
x = [- 6 ± √16] / -2
x = [- 6 ± 4] / -2
x' = [- 6 + 4] / -2 = -2 / -2 = 1
x'' = [- 6 - 4] / 2 = -10 / -2 = 5
S = {1, 5}
Espero ter ajudado. Valeu!
a = 1; b = -6; c = 5
x = [- b ± √(b² - 4ac)] / 2a
x = [- (-6) ± √([-6]² - 4 . 1 . 5)] / 2 . 1
x = [6 ± √(36 - 20)] / 2
x = [6 ± √16] / 2
x = [6 ± 4] / 2
x' = [6 + 4] / 2 = 10 / 2 = 5
x'' = [6 - 4] / 2 = 2 / 2 = 1
S = {1, 5}
b) -x² + 6x - 5 = 0
x = [- b ± √(b² - 4ac)] / 2a
x = [- 6 ± √(6² - 4 . [-1] . [-5])] / 2 . (-1)
x = [- 6 ± √(36 - 20)] / -2
x = [- 6 ± √16] / -2
x = [- 6 ± 4] / -2
x' = [- 6 + 4] / -2 = -2 / -2 = 1
x'' = [- 6 - 4] / 2 = -10 / -2 = 5
S = {1, 5}
Espero ter ajudado. Valeu!
Oimeuamor111:
ajudou muito
Perguntas similares
7 anos atrás
7 anos atrás
7 anos atrás
9 anos atrás
9 anos atrás
9 anos atrás
9 anos atrás